2011
DOI: 10.1177/1359104510384338
|View full text |Cite
|
Sign up to set email alerts
|

Parenting training in the community: linking process to outcome

Abstract: This pilot study examines the effectiveness of the Parents Together Community Course(i) (a six week preventative version of the Parents Plus Early Years Programme) in reducing parent-reported behaviour problems in pre-school and school aged children. It also investigates if there is an association between process ratings on a weekly session rating form (WSRF) and client outcome. Thirty-one parents who completed the course filled out pre and post outcome measures (namely the Strengths and Difficulties Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Furthermore both PPEY group formats significantly reduced parent-reported child total difficulties and significantly improved parenting satisfaction. This supports the findings of Kilroy et al, (2011) that a preventative version of the PPEY program in the community was effective in reducing parent-reported behavior problems in preschool and school-aged children and Hand et al, (2013) who found the Parents Plus Children's Programme delivered in community settings significantly improved measures of child behavior, parental stress, and parent satisfaction. These findings demonstrate that both the seven-week and single workshop PPEY group intervention may be effective early interventions as part of a community-led approach to child and adolescent mental health.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore both PPEY group formats significantly reduced parent-reported child total difficulties and significantly improved parenting satisfaction. This supports the findings of Kilroy et al, (2011) that a preventative version of the PPEY program in the community was effective in reducing parent-reported behavior problems in preschool and school-aged children and Hand et al, (2013) who found the Parents Plus Children's Programme delivered in community settings significantly improved measures of child behavior, parental stress, and parent satisfaction. These findings demonstrate that both the seven-week and single workshop PPEY group intervention may be effective early interventions as part of a community-led approach to child and adolescent mental health.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, the PPEY Program has been shown to reduce conduct problems, hyperactivity, and parental stress and to help parents move significantly closer to their goals when conducted in a clinical setting by mental health professionals (Griffin, Guerin, Sharry, & Drumm, 2010); however, many parents display limited attendance with clinic-based programs and are less likely to complete treatment (Kazdin, Mazurick, & Bass, 1993), with some parents reporting feeling stigma attached to attending child and adolescent mental health services (Bradby et al, 2007). To overcome these challenges, there is growing interest in delivering communitybased parenting programs (Hand, Ní Raghallaigh, Cuppage, Coyle, & Sharry, 2012;Kilroy, Sharry, Flood, & Guerin, 2011;McGilloway et al, 2012).…”
Section: Parents Plus Programmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore impossible to disentangle the relative efficacy of each process in isolation (Kaminski et al 2008). The existing literature on parenting programs is thus mostly oriented towards effectiveness of outcomes rather than towards processes used to induce change over time (Hogard 2008;Kilroy et al 2011;Westen et al 2004). By contrast, 'Lou & us' attempts to isolate metacognition as the core process that promotes positive parenting.…”
Section: Introductionmentioning
confidence: 93%